The effects of combination-therapy of tocilizumab and baricitinib on the management of severe COVID-19 cases: a randomized open-label clinical trial - Dastan, Farzaneh; Jamaati, Hamidreza; Barati, Saghar; Varmazyar, Shahrzad; Yousefian, Sahar; Niknami, Elmira; Tabarsi, Payam (Frontiers in Pharmacology, 2023)
Background: Tocilizumab and baricitinib are considered standard treatments for hospitalized COVID-19 patients with an inflammatory status. However, the effects of co-administering these medications aiming for more rapid patient recovery are controversial among practitioners. The potential benefits include the rapid improvement of patients and regulation of the immune system, and the potential risks include the increased chance of serious adverse events, including infections.This study aimed to investigate the effects of co-administering these two medications on the 28-day mortality rate, other efficacy parameters, and safety issues. Methods: In this randomized open-label trial, 68 patients were recruited. The study was conducted at Dr. Masih Daneshvari Hospital during 6 months (from 21 March 2022 to 23 August 2022). Severely